Evaluation of Post-Quantum Distributed Ledger Cryptography - Robert E. Campbell Sr. (The Journal of The British Blockchain Association, 2019)
This paper evaluates the current cybersecurity vulnerability of the prolific use of Elliptical Curve Digital Signature Algorithm (ECDSA) cryptography in use by the Bitcoin Core, Ethereum, Bitcoin Cash, and enterprise blockchains such as Multi-Chain and Hyperledger projects Fabric, and Sawtooth Lake. These blockchains are being usedin media, health, finance, transportation and government with little understanding, acknowledgment of the risk and no known plans for mitigation and migration to safer public-key cryptography. The second aim is to evaluate ECDSA against the threat of Quantum Computing and propose the most practical National Institute of Standards and Technology (NIST) Post-Quantum Cryptography candidate algorithm lattice-based cryptography countermeasure that can be implemented near-term and provide a basis for a coordinated industry-wide lattice-based public-key implementation. Commercial quantum computing research and development is rapid and unpredictable, and it is difficult to predict the arrival of fault-tolerant quantum computing. The current state of covert and classified quantum computing research andadvancement is unknown and therefore, it would be a significant risk to blockchain and Internet technologies to delay or wait for the publication of draft standards. Since there are many hurdles Post-Quantum Cryptography (PQC) must overcome for standardisation, coordinated large-scale testing and evaluation should commence promptly.